The first case report of polymerase proofreading-associated polyposis in POLD1 variant, c.1433G>A p.S478N, in Japan. (17th June 2020) - Ito, Tetsuya; Nomizu, Tadashi; Eguchi, Hidetaka; Kamae, Nao; Dechamethakun, Sariya; Akama, Yoshinori; Endo, Goichi; Sugano, Kokichi; Yoshida, Teruhiko; Okazaki, Yasushi; Ishida, Hideyuki
Abstract: Polymerase proofreading-associated polyposis, caused by germline variants in the exonuclease domains of POLD1 and POLE, is a dominantly inherited rare condition characterized by oligo-adenomatous polyposis and increased risk of colorectal cancer, endometrial cancer and brain tumours. We report the first Japanese case of polymerase proofreading-associated polyposis carrying a POLD1 variant. The proband was a Japanese woman who had undergone resections of early colorectal carcinomas repeatedly and a hysterectomy with bilateral oophorectomy for endometrial cancer, all of which were diagnosed within 2 years after the first colectomy at 49 year old. Colonoscopic examinations demonstrated at least 14 non-cancerous polypoid lesions, some of which were histologically confirmed to be adenoma. Multigene panel sequencing identified a missense variant in POLD1 (c.1433G>A). Although her relatives did not undergo genetic testing, her father and paternal grandfather died of brain tumours at 53 and ~30 years of age, respectively. Abstract : We report the first Japanese case of polymerase proofreading-associated polyposis carrying a POLD1 variant.